Assessment of coliform bacteria contamination in the Brantas River as a bioindicator of sanitation and clean water source quality - Wardah, Nihaya Nailatul; Kartikaningsih, Hartati; Koentjoro, Maharani Pertiwi (Jurnal Pembangunan dan Alam Lestari, 2026)
River monitoring for bacterial contamination plays a vital role in preventing waterborne disease transmission and safeguarding public health, particularly in densely populated areas with inadequate sanitation infrastructure. Human activities such as domestic wastewater discharge, improper waste disposal, and agricultural runoff significantly influence microbial communities in aquatic ecosystems and may increase the spread of pathogenic microorganisms and antibiotic resistance. Escherichia coli (E. coli) is widely recognized as a reliable indicator of fecal contamination and overall water quality because its presence suggests potential contamination by enteric pathogens that pose risks to human health. This study aimed to assess coliform bacteria levels in river water as bioindicators of sanitation conditions and the quality of clean water sources. A descriptive-quantitative research design was employed to obtain measurable and systematic data. Water samples were collected from three river locations situated in areas characterized by poor sanitation systems. The selected sites represent zones where domestic activities directly interact with river water, potentially contributing to microbial pollution. Coliform bacteria concentrations were analyzed using the Most Probable Number (MPN) method to estimate bacterial density in each sample. The results demonstrated that coliform contamination levels varied across sampling points and reflected surrounding sanitation conditions. Elevated coliform counts indicated significant fecal pollution, confirming that coliform bacteria are effective bioindicators for evaluating sanitation performance and clean water source quality in riverine environments.